PENGARUH KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN OPERASIONAL PADA PT. PUPUK INDONESIA (PERSERO) KANTOR MAKASSAR - Imam Fauzan; Sitti Marhumi; Muhammad Akib (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the influence of employee competence on operational employee performance at PT. Pupuk Indonesia (Persero) Makassar Office. This study used a quantitative approach with 40 employees as respondents. Data collection was conducted through a questionnaire using a Likert scale. Data analysis was conducted using descriptive statistics, instrument testing, simple linear regression analysis, and hypothesis testing using the t-test with SPSS. The results show that employee competence has a positive and significant influence on operational employee performance (t = 9.914, sig. < 0.001). The coefficient of determination (R²) was 0.721, meaning employee competence explains 72.1% of the variation in operational performance. The company is advised to continuously improve training programs and periodically evaluate competency to support optimal operational performance.